Radiation dose management in the nuclear industry. (ICE Publishing, 1995)
The revised recommendations of the ICRP in its Publication 60 have led to significant changes in attitudes and to a new culture of radiological protection. Lower dose limits and the requirement to ensure that exposure is as low as reasonably achievable means that detailed attention must be given to radiological aspects from design, through commissioning, operation and maintenance, to eventual decommissioning. In this book the authors discuss the complex solutions to the problems of dose reduction, involving a scientific approach to the understanding of the sources of exposure, good engineering in the design and operation of facilities and efficient management of radiation protection.